Risks for Mental Illness in Indigenous Australian Children: A Descriptive Study Demonstrating High Levels of Vulnerability. - Twizeyemariya, Asterie; Guy, Sophie; Furber, Gareth; Segal, Leonie (My University, 2017)
Context: Mental illness is a high source of disease burden across the globe. Mental illness is now understood as largely developmental, with its genesis at least in part in adverse childhood experiences. We sought to estimate the prevalence of childhood risks for poor mental health in Indigenous Australian children, noting that Indigenous Australians by virtue of their history of traumatic colonization and dispossession, child removal, and racism are potentially at greater risk. Methods: We conducted a descriptive study of the modifiable risks and adversities associated with mental illness in Australian Indigenous children (infancy to 10 years), using data from the Longitudinal Study of Indigenous Children (LSIC), a cohort of 1,671 infants enrolled in 2008 and followed up annually. Risk factors of interest were identified from a comprehensive literature review of childhood determinants of adult mental illness by Fryers and Brugha (2013). The age-category prevalence of individual risks and a multiple-risk score were computed using data extracted from 6 waves of LSIC. Findings: The analytic data comprised 8,378 person-observations from the first 6 waves. Children in LSIC experience high rates of adversities. In utero, nearly 50% were exposed to smoking and 22% to alcohol. As infants, 42.5% were not living with both birth parents. Over two-thirds of survey children were in households that had experienced, in the previous 12 months, 3 or more major life events; 22% to 26% lived in households with a drug or alcohol problem; and 18% were exposed to domestic violence (41% were ever-exposed to age 10). At school, nearly 40% of children were bullied. Over 45% of children aged 6 to 10 years were exposed to 6 or more risks for mental illness. Few children (< 2%) were exposed to low parental warmth and, despite the high exposure to adversities, less than 5% of children report low self-confidence. This suggests considerable resilience. More than 1 in 4 children had conduct problems in the clinical range and more than 1 in 5 were experiencing high psychological distress. Conclusions: Indigenous children in Australia face extreme levels of multiple disadvantage, exposing many to current psychological distress and high risk of developing mental illness, despite considerable resilience. For policymakers, this is a call for preventive action targeting the multiple risk factors already present in childhood. An integrated service system offering culturally appropriate, high-quality early childhood education services, linked to infant, child, adolescent, and family mental health services, and intensive family support services will be crucial in addressing this public health crisis.
Milbank Quarterly
Keywords: Health and wellbeing; Health and wellbeing